Make-Up Therapy as Kiara Leswara's Personal Branding on YouTube (Oratio Directa, 2022)
This study examines how Kiara Leswara's Make-Up Therapy content constructs personal branding on YouTube. It uses a qualitative descriptive approach through online observation of the Kiara Leswara channel, documentation, and literature review, applying Rampersad's eleven criteria for authentic personal branding. The source reports 82 videos across eight playlists, including 15 lifestyle videos, and presents seven high-engagement examples from beauty-related playlists. However, the reported observation period is inconsistent, referring both to 2021 only and to 2021-2022; upload dates, coding procedures, and archived metrics are not fully documented. The analysis identifies evidence for authenticity, integrity, consistency, specialization, authority, differentiation, relevance, visibility, persistence, goodwill, and performance. The strongest claims concern consistency of beauty content, relevance to the target audience, persistence in production, and goodwill expressed through appreciative interaction and self-acceptance messages. Make-Up Therapy functions as a distinctive editorial label combining tutorials with self-improvement narratives; the study does not provide clinical evidence that makeup constitutes mental-health therapy. Engagement figures support descriptive comparison but cannot independently establish audience trust, brand authenticity, or causal effects.
Keywords: Personal branding; Make-up therapy; YouTube; Beauty influencer; Kiara Leswara